Synthesis and characterization of new aromatic polyesters containing cardo decahydronaphthalene groups - Honkhambe, Pandurang N.; Bhairamadgi, Nagendra S.; Biyani, Mahesh V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (European Polymer Journal, 2010)
Three cardo bisphenols containing decahydronaphthalene group viz., 4,4'-(octahydro-2(1H)-naphthylidene)bisphenol, 4,4'-(octahydro-2(1H)-naphthylidene)bis-3-methylphenol and 4,4'-(octahydro-2(1H)-naphthylidene)bis-3,5-dimethylphenol were synthesized starting from commercially available 2-naphthol and were utilized for synthesis of new aromatic polyesters by phase transfer-catalyzed interfacial polycondensation with isophthaloyl chloride, terephthaloyl chloride and a mixture of isophthaloyl chloride and terephthaloyl chloride (50:50 mol %). Inherent viscosities and number average molecular weights (M(n)) of polyesters were in the range 0.35-0.84 dL/g and 13300-48,500 (Gel Permeation Chromatography, polystyrene standard), respectively. Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methy1-2-pyrrolidinone at room temperature and could be cast into tough, transparent and flexible films from their chloroform solutions. Wide-angle X-ray diffraction measurements revealed the amorphous nature of polyesters. The glass transition temperature of polyesters was in the range 207-287 degrees C. The temperature at 10% weight loss (T(10)), determined from thermogravimetric analysis of polyesters, was in the range 425-460 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: bisphenol; Cardo; Decahydronaphthalene; polyester; Structure-property relationship

Synthesis and characterization of new aromatic polyesters containing pendent naphthyl units - Honkhambe, Pandurang N.; Biyani, Mahesh V.; Bhairamadgi, Nagendra S.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2010)
Two bisphenols, viz., 4,4'-[1-(2-naphthaleny-1)ethylidene]bisphenol and 4,4'-[1-(2-naphthalenyl) ethylidene]bis-3-methylphenol were prepared by condensation of commercially available 2-acetonaphthanone with phenol and o-cresol, respectively. A series of new aromatic polyesters containing pendent naphthyl units was synthesized by phase-transfer-catalyzed interfacial polycondensation of these bisphenols with isophthaloyl chloride, terephthaloyl chloride, and a mixture of isophthaloyl chlorideiterephthaloyl chloride (50 : 50 mol %). Inherent viscosities of polyesters were in the range 0.83-1.76 dL g(-1), while number average molecular weights (M(n)) were in the range 61,000-235,000 g mol(-1). Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, m-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetarnide, and 1-methyl-2-pyrrolidinone at room temperature. Tough, transparent, and flexible films were cast from a solution of polyesters in chloroform. X-Ray diffraction measurements displayed a broad halo at 20 congruent to 19 degrees indicating the amorphous nature of polyesters. Glass transition temperatures of polyesters were in the range 209-259 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of polyesters was in the range 435-500 degrees C indicating their good thermal stability. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 2545-2552, 2010
Keywords: Aromatic polyesters; bisphenol; interfacial polycondensation; pendent naphthyl units

Synthesis and characterization of polyesters from 2,3-bis (4 `-hydroxy phenyl) quinoxaline and 2,3-bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline - Patil, V. B.; Medhi, M.; Bhairamadgi, Nagendra S.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
Two bisphenols containing pendant, quinoxaline moiety; 2,3-bis (4'-hydroxy phenyl) quinoxaline (BHPQ) and 2,3-bis (2'-hydroxynaphthalene-6-yl) quinoxaline (BHNQ) were synthesized and characterized by FT-IR, (1)H, (13)C NMR and mass spectrometry. Aromatic polyesters and copolyesters were prepared by interfacial polymerization from BHPQ or BHNQ and isophthaloyl chloride or terephthaloyl chloride or a mixture of different mole proportions of (IPC + TPC). These polyesters and copolyesters were characterized by spectroscopic technique, viscosity measurement, solubility, thermal stability. DSC and XRD. Polymers had moderate to high molecular weights as evidenced by the inherent viscosities in the range 0.35-0.78 dL/g for BHPQ series and 0.27-0.52 dL/g for BHNQ series. BHPQ polyesters and copolyesters dissolved in m-cresol, NMP and conc. H(2)SO(4) whereas, BHNQ polyesters and copolyesters were readily soluble in NMP, DMAc, (TCE + phenol) and partly soluble in solvent like CHCl(3), pyridine, etc. Wide angle X-ray diffraction (WAXD) results showed that introduction of quinoxaline moiety into polymer chain and aromatic phenyl/rigid naphthyl structures lead to crystalinity. Differentional scanning calorimetry of BHNQ polyesters showed the glass transition temperatures in the range of 131-151 degrees C. BHPQ polyesters did not show any weight loss below 330 degrees C and retained 27-55% weight at 900 degrees C when investigated by TGA under nitrogen atmosphere demonstrating good thermal stability BHNQderived polyesters showed initial decomposition temperatures in range 211-234 degrees C. The structure-property relationships for the mentioned polyesters are analyzed, as these polyesters are of interest as materials for electronics, microelectronics and membrane separation. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 2; 3-Bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline; 3-Bis (4 `-hydroxy phenyl) quinoxaline; Aromatic polyesters; Glass transition temperature; solubility; Thermal properties

Synthesis and characterization of soluble polyamides from bis-[(4 `-aminobenzyl)-4-benzamide] ether and various diacids - Patil, A. S.; Sayyed, M. M.; Bhairamadgi, Nagendra S.; Han, Sung-Hwan; Maldar, Noormahamad N. (Polymer Bulletin, 2011)
New aromatic diamine containing preformed amide, ether, and methylene; bis-[(4'-aminobenzyl)-4-benzamide] ether (BABE), was synthesized and characterized by FT-IR, NMR, and mass spectrometry. Aromatic-aliphatic polyamides were prepared from BABE with aliphatic/aromatic diacids via Yamazaki's polymerization. The polyamides were characterized by FT-IR, (1)H NMR, inherent viscosity [eta(inh)], solubility tests, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA], and X-ray diffraction [XRD]. Polyamides had inherent viscosities 0.35-0.84 dL/g, soluble in aprotic polar solvents like N-methyl-2-pyrrolidone, N, N-dimethyl acetamide and dimethyl sulphoxide containing LiCl due to an amorphous to partially crystalline morphology; as XRD patterns indicated. DSC analysis of polyamides showed glass transition temperatures 166-268 A degrees C. Polyamides showed high thermal stability as they did not degrade below 300 A degrees C, had 10% weight loss temperature higher than 375 A degrees C, and the char yields at 900 A degrees C were 22-55%; indicating potential applications as engineering materials.
Keywords: Aryl-ether and methylene linkages; Bis-[(4 `-aminobenzyl)-4-benzamide] ether; Direct phosphorylative polycondensation; Soluble aromatic-aliphatic polyamides; Thermal properties